2016
DOI: 10.1007/s40194-016-0355-3
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating decision-making by choosing an NDT method based on information need

Abstract: This paper discusses the choice of an NDT method (non-destructive testing) from an information need perspective. It bridges the gap between technical methods, monitoring procedures and the need for information in an industrial application. The simple pull approach described starts from the decision that needs to be taken rather than from a previous data push procedure. That makes it more likely to match the method with the actual need, which leads to more effective and efficient evaluations. The pull approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Therefore, one challenge was to identify a method sufficient for the organization to use. During the years, different solutions developed depending on the information needed from the measurements, e.g., radius gauges, impressions, scanning, and cameras [13,14,19,20]. The suggested use of the methods was also developing towards a more proactive approach.…”
Section: Assessment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one challenge was to identify a method sufficient for the organization to use. During the years, different solutions developed depending on the information needed from the measurements, e.g., radius gauges, impressions, scanning, and cameras [13,14,19,20]. The suggested use of the methods was also developing towards a more proactive approach.…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Based on theory and what had been seen in the studies conducted, a model was suggested, called PULL approach for quality assurance [13] (see Fig. 4).…”
Section: Quality Assurancementioning
confidence: 99%
“…Ericson Öberg and Hammersberg describe different scenarios depending on the information need of the welder, programmer, or engineer [23,24]. Depending on the information need, different methods for measuring weld toe radius are suitable.…”
Section: Measurement Systems For Quality Assurance Of the Weld Surfacmentioning
confidence: 99%